URGENSI KOMPETENSI GURU DALAM PEMBINAAN KARAKTER SISWA DI MTSN PANCUNG SOAL KABUPATEN PESISIR SELATAN - Ramadhani Ramadhani; Efendi Efendi (STKIP Pesisir Selatan, 2019)
This study aims to (a) To describe the urgency of pedagogical competence in fostering student character (b) To describe the urgency of personality competence in fostering student character (c) To describe the urgency of social competence in fostering student character (d) To describe the urgency of professional competence in coaching student character. Retrieval of data using qualitative descriptive methods to describe and describe the urgency of teacher competence in fostering student character in MTsN Pancung Soal in accordance with what it is and analyze it scientifically. Indicators of character development that need to be done in learning are reviewed from 4 (four) aspects of teacher competency, namely: (1) the urgency of pedagogical competencies in the form of understanding character values for students, applying character values in the implementation of learning, instilling character values in utilizing learning technology, evaluating learning outcomes and actualizing student potential. (2) the urgency of personality competence in the form of inculcation of character values in loving position, being fair to all students, being patient and calm, and building authority as educators. (3) the urgency of social competence in the form of instilling values of politeness in oral and written communication, the use of information technology and functional communication, associating effectively with the whole school community and student guardians. (4) the urgency of professional competence in the form of inculcation of character values in the educational foundation as well as in learning materials.